Pengaruh Interval Pemotongan Rumput Brachiaria humidicola (Rendle) Schweick terhadap Konsentrasi Amonia dan Asam Lemak Terbang (In Vitro) - Mansyur Mansyur; L. Abdullah; H. Djuned; A.R. Tarmidi; T. Dhalika (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
The existence of weeds significantly depressed productivity and quality of herbage. Physically weed controlled by defoliation could be expected to sustain quality and production of herbage, and able to control weeds expansion. The aims of study were to find the effect of interval defoliations of B. humidicola that invited by C. odorata and its effect on concentration of ammonia and volatile fatty acid of B. humidicola herbage (in vitro). The experiment was carried out at Laboratory of Agrostology, Faculty of Animal Science Bogor Agricultural University. In vitro digestibility of herbage was analyzed at Ruminant Nutrition and Feed Chemistry Laboratory, Faculty of Animal Husbandry, Padjadjaran University. Split plot design in time was used in the field experiment. The treatments were nine different planting methods and different defoliation intervals. Defoliation times are divided on the first defoliation and the last defoliation. The results showed that concentration of both ammonia and volatile fatty acid of herbage, which defoliated every 60 days were found significantly higher than those defoliated every 30 days and 90 days. Present and defoliation of C. odorata didn’t give significant effect on the concentration of ammonia and volatile fatty acid of B. humidicola herbage.